CTE Workshop Proc. 2022
DOI: 10.55056/cte.100
|View full text |Cite
|
Sign up to set email alerts
|

ICT and current trends as a path to STEM education: implementation and prospects

Abstract: The aim of the study is to build a model for the introduction of STEM education in institutions of general secondary education, to demonstrate the experience of using ICT in STEM education. Research objectives: to determine the role and place of information and communication technologies in the model of introduction of STEM education in general secondary education institutions for the formation of key competencies; to find innovative solutions to create conditions that will promote the interest of student yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…This article highlights further research by the authors, begun in [8, 20-24, 26, 115, 167, 232]. The aim of the article "ICT and current trends as a path to STEM education: implementation and prospects" [110] by Natalia S. Lukychova (figure 5), Nataliia V. Osypova, Galina S. Yuzbasheva is to build a model for the introduction of STEM education in institutions of general xxiv Synergetics as a scientific area of research is in demand by society. The context of synergetics makes it possible for scientists of different specializations to interact fruitfully in the language of systematic understanding and search for new solutions.…”
Section: Articles Overview 21 Session 1: Digital Transformation Of Ed...mentioning
confidence: 83%
“…This article highlights further research by the authors, begun in [8, 20-24, 26, 115, 167, 232]. The aim of the article "ICT and current trends as a path to STEM education: implementation and prospects" [110] by Natalia S. Lukychova (figure 5), Nataliia V. Osypova, Galina S. Yuzbasheva is to build a model for the introduction of STEM education in institutions of general xxiv Synergetics as a scientific area of research is in demand by society. The context of synergetics makes it possible for scientists of different specializations to interact fruitfully in the language of systematic understanding and search for new solutions.…”
Section: Articles Overview 21 Session 1: Digital Transformation Of Ed...mentioning
confidence: 83%
“…However, in 2018, two related studies Terzieva et al (2019) and Manosuttirit (2019) were found. From 2019 to 2022, there were 3 research results each year (Barakabitze et al, 2019;Birzina & Pigozne, 2020;El Mawas et al, 2019;Hidiroglu & Karakas, 2022;Hrynevych et al, 2021;Istrate et al, 2019;Khaokhajorn et al, 2020;Lukychova et al, 2022;Mangahas et al, 2022;Xu & Ouyang, 2022;Yang & Baldwin, 2020). It could be said that considering the role of IT in STEM education is an important issue, gaining more and more research attention, this trend will continue throughout 2023 and the ensuing years (see Figure 2).…”
Section: Datementioning
confidence: 99%
“…Sea en un modelo más empírico o en otro más volcado en el pensamiento científico (McFarlane y Sakellariou, 2002), las tecnologías digitales pueden y deben aportar mucho a los procesos de enseñanzaaprendizaje de las ciencias en particular y de las áreas STEM en general. La implementación de las TIC en la enseñanza de las materias STEM permite entre otras cosas, incrementar la calidad y efectividad de la formación en dichas áreas, aumentar el nivel de motivación de los participantes en el proceso de enseñanza-aprendizaje, produce una mejora en la calidad del conocimiento de dichas asignaturas y además contribuye al desarrollo de las competencias clave por parte del alumnado (Kanematsu y Barry, 2016;Lukychova et al, 2022). Las TIC son unas excelentes herramientas y recursos para transformar la educación de las STEM desde la innovación, aunque es cierto que para ello hace falta que se den ciertos requerimientos que no se pueden pasar por alto: capacitación del profesorado en el uso e implementación de estas herramientas y recursos; aumento de la dotación a los centros de dispositivos, equipos y aplicaciones; formación continua, seguimiento, evaluación y actualización constante y donde la formación de grupos de trabajo o seminarios puede ser una excelente idea para mantener viva esta inquietud (Barakabitze et al, 2019).…”
Section: Las Tecnologías Digitales En La Educación Stemunclassified